MODEL PENGEMBANGAN KECERDASAN SPIRITUAL DALAM PEMBELAJARAN AKHLAK DI PESANTREN MODERN INDONESIA - Arlina Arlina; Didik Santoso (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2020)
The study aims at comparing the models of the spiritual intelligence development in learning morals subject implemented in the boarding schools of Raudhatul Hasanah Medan, Prof Dr. Hamka Padang, Darunnajah Jakarta, and Al-Kamal Blitar. This research used qualitative method. The data collection techniques were observations, interviews, documents, and focused group discussions. The results are (1) Spiritual intelligence is developed through preparatory learning, learning in the class, and outside of the class, (2) There are four similarities that are preparation of teaching, learning in the class, connection of learning in the class with outside of the class, and the systematic planning between learning in and out of the classroom, (3) There are six differences in the separation of male and female students in classroom learning, as well as separation of learning activities outside of the classroom, the role of teachers in classroom learning, the use of applications to monitor classroom and outside the classroom, management of learning outside the classroom, and the implementation of learning in and out of the classroom (4) The causes of the similarities and differences are the initial background of the boarding schools’ founding, the founders’ point of view, the boarding schools’ developmental process, the management system, and the influence of stakeholder policy.